Sengketa Batas Wilayah Dalam Sistem Pemerintah Daerah (Studi Pada Batas Wilayah Kabupaten Sintang Dan Kabupaten Sekadau) - Ferdinan Paulus Anyab (Postgraduate University of Merdeka Malang, 2021)
This study aims to analyze the settlement of boundary disputes that are available in the Indonesian legal system, analyze the factors that cause boundary disputes in the expansion of the Autonomous Region in Sintang Regency and Sekadau Regency. The type of research conducted is juridical-empirical. The results of the study conclude that: First, the pattern of settlement of territorial boundary disputes is generally through two channels, namely: non-legal settlement of border disputes, and legal settlement. Non-legally mediated by the Ministry of Home Affairs and the Governor. Meanwhile, legal dispute resolution is pursued through litigation. The occurrence of territorial boundary disputes is triggered by the process of regional expansion which does not require regional boundaries as a legal requirement in regional expansion. The requirements that are met are more technical, physical and political. In territorial boundary disputes with district governments, the role of the provincial government is only as a facilitator according to the level of the case dispute.DOI: https://doi.org/10.26905/mlj.v2i2.7156